A MATLAB framework for forecasting optimal flow releases in a multi-storage system for flood control. (March 2020) - Leon, Arturo S.; Tang, Yun; Qin, Li; Chen, Duan
Abstract: This paper presents a MATLAB framework for forecasting optimal flow releases in a multi-storage system for flood control. This framework combines four widely-used models intended for (1) performing hydrologic analysis for a watershed and for level-pool routing in the storage systems, (2) simulating river inundation, (3) solving the optimization problem of determining hourly optimal flow releases in a multi-storage system, and (4) data management and plotting. The integration of all software is performed in MATLAB, which is a state-of-the-art and an easy-to-use environment for integrating computation, visualization, and programming. This paper focuses on (1) presenting the MATLAB scripts for interfacing the aforementioned four software, (2) describing the rationale for the objective function of the optimization, and (3) demonstrating the practical use of the MATLAB framework by applying it to the operation of a hypothetical eight-pond system in the Cypress Creek watershed in Houston, Texas. The results of the aforementioned application show that this framework could help in mitigating flooding. Highlights: This paper presents MATLAB scripts for interfacing four models of hydrology, hydraulics, optimization and data management. The MATLAB scripts are exemplified through the flood control operation of a hypothetical eight-pond system.